Tailoring the chemistry and the nano‐architecture of organic thin films using cold plasma processes. Issue 11 (23rd May 2017) - Thiry, Damien; Chauvin, Adrien; El Mel, Abdel‐Aziz; Cardinaud, Christophe; Hamon, Jonathan; Gautron, Eric; Stephant, Nicolas; Granier, Agnès; Tessier, Pierre‐Yves
Abstract : In this work, we report on the development of a novel approach based on three different plasma‐based processes (i.e., plasma polymerization, magnetron sputtering, and plasma etching) to fabricate nanostructured polymer thin films. Our strategy involves at first the formation of nitrogen containing plasma polymer film subsequently covered by silver nanoparticles, serving as a hard etching mask, using magnetron sputtering. Then, the exposition of the material to a complex mixture of highly reactive radicals, ions, and photons results in the structuring at the nanoscale of the functionalized plasma polymer films. It has been demonstrated that the dimension, the shape (e.g, . nano‐dome, nano‐cone, nano‐valley, inter‐connected porous network, …) and the chemical composition of the nano‐objects can be tailored by adjusting the plasma parameters in each step of our overall procedure. Abstract : An original procedure aiming to control the nano‐organization and the chemical composition of functionalized plasma polymer films is established. This approach is based on the combination of three different plasma‐based processes: the plasma polymerization, the magnetron sputtering, and the plasma etching techniques. The whole set of our results clearly demonstrate the attractiveness of our method for the fabrication of functionalized and nanostructured organic‐based coatings with tunable functionalities and morphology.